Upcycling Perca Brokat dengan Tule Menggunakan Metode Sirkular Resource-Pressure - Hafidzah, Serena; Santoso, Ratna Endah (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The majority of textiles today are inorganic waste that requires a lengthy processing process to decompose. Although there are various methods and stages for processing textile scraps, there are still limited techniques used for processing brocade and tulle scraps. This design represents one sustainable waste utilization option using the practice of upcycling brocade scraps into vests, based on the resource-pressure circular design method designed according to six design parameters, namely product mass, primary material content, product lifespan, manufacturing waste, recycling, and decomposition. The objective of this method is to maximize the utilization of secondary raw materials (waste) in production, transforming brocade and tulle scraps into vest garments that serve as versatile and unisex complements for various occasions.